The Relevance of Curriculum Merdeka Belajar Policies with The Formation of Religious Character - Abidin, Zainal (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2023)
This research aims to analyze in depth the substance of the independent learning curriculum policy as a new policy in improving the quality of education in the context of today's religious character education. Along the way, the curriculum always changes which is interpreted as the improvement of the previous curriculum. The spirit built in the independent learning curriculum is to create learning quality that is able to respond to developments in globalization. Whatever the form of improvement and innovation is desired, of course it cannot be separated from the three aspects of education, those are the development of cognitive, affective and psychomotor aspects, and the main goal of national education related to the aspect of building students' positive behaviours, because this is the main foundation in the educational process. Likewise with the independent curriculum, apart from aiming at developing competencies, increasing interests and talents, it also aims at developing the character of students. This research uses a qualitative research approach with a literature study research method. The stages in data collection are carried out through reviewing books, journals and related scientific works. Based on the study of various literature, the results are obtained that the independent learning curriculum policy is in line with the concept of religious character education or religious humanism curriculum, both in terms of objectives, learning processes, methods and evaluation, because students are given sufficient space to develop their potentials through activities in the educational unit settings.